The Development Of Problem-Based Mathematics Learning Model For The First Year Vocational High School Students - Indah Pertiwi; Imam Sofi'i (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This study is intended to produce a problem-based mathematics learning model for SMK (Vocational High School). The development used the Plomp development model. The procedures are: (1) preliminary study; (2) the stage of developing or making a prototype; and (3) assessment phase. The feasibility of a problem-based mathematics learning model for SMK  that is developed refers to the product quality criteria that are valid, practical, and effective. The development of problem-based mathematics learning models for Vocational Schools involved two experts and three practitioners. The objects in this study were students of first year  vocational high schools in South Tangerang City and three mathematics teachers. Sampling techniques used in this study are  purposive sampling, stratified random sampling, and proportional random sampling. The instruments used consist  of: instruments for evaluating validity which included validation sheets, instruments for assessing practicality which included practicality assessment sheets from teachers and students, and observations sheets for the implementation of learning, as well as effectiveness assessment sheets namely learning achievement tests. The results showed that the learning model developed includes syntax, social systems, reaction principles, support systems, and learning impacts that meet valid, practical, and effective criteria